Prevalence of musculoskeletal symptoms in university workers Barquisimeto, Venezuela, 2014. (Revista Venezolana de Salud Pública, 2018)
A cross-sectional descriptive study was carried out in order to determine the prevalence of musculoskeletal symptoms in university workers. The sample consisted of 347 administrative workers, teachers and workers selected from the population of workers of the Centroccidental University "Lisandro Alvarado" of Barquisimeto (Venezuela). The Standardized Nordic Questionnaire was applied to collect data on musculoskeletal symptoms.
Keywords: prevalence rate; musculoskeletal symptoms; nordic questionnaire; ergonomics; workers; University